Analysis of a Persuasive Video on YouTube: A Collaboration between the Indonesian Ministry of Health and the Nahdlatul Ulama to Promote COVID-19 Vaccination in Indonesia - Cholifah, Yuristia Wira; Adrianto, Aditya Eko (Universitas Ahmad Dahlan, 2023)
The COVID-19 pandemic in Indonesia led to the collapse of national health facilities and the economy, which resulted in the acceleration of the invention of COVID-19 vaccines. However, only 54.9% of the population is willing to be vaccinated due to fake news or hoaxes. The government urges the public to obey regulations, especially in public spaces, and intensifies socialization through various media, such as YouTube. This study aims to determine the critical elements that compose the video on the YouTube channel so that it can be used as a medium to persuade the wider community. This study used qualitative methods to collect visual and textual data from purposively selected videos and screenshots, which were analyzed using communication theory for persuasion and a constructionist approach to interpret the data and identify variables such as the message's source, characteristics of the recipient, and purpose of the message. The Indonesian Ministry of Health and the Nahdlatul Ulama Executive Board collaborated to create a 2-minute, 53-second video on the importance of vaccination in Indonesia, particularly for Muslims. The video features PBNU's Health Head, dr. Syahrizal Syarif effectively educates the public on vaccination's significance and emphasizes community unity to support the government's vaccination program. The communicator in the video successfully positioned himself as a religious leader and doctor. The video is effective in communicating three key messages. It uses persuasive communication theory, using YouTube's power to influence people's opinions, suggesting that the government should use digital platforms to deliver more messages to the citizens in the future.